A rapid ceramic coating and method of making the same

CN122810708BActive Publication Date: 2026-11-03BEIJING INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202611291973.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2026-08-25
Publication Date
2026-11-03
Estimated Expiration
2046-08-25

Smart Images

  • Figure CN122810708B_ABST
    Figure CN122810708B_ABST
Patent Text Reader

Abstract

The present application relates to a kind of quick ceramming coating and its preparation method, belong to composite material surface protection technical field.The preparation raw material of quick ceramming coating includes coating composition, the composition includes grafting modified base 35~50% by mass percentage, quick ceramming core phase 25~35%, synergistic reinforcing phase 9~25%, functional auxiliary agent 3~8% and mixed dispersion solvent 12~25%;Grafting modified base is composed of KH560 and KH570 double grafting modified methyl phenyl organosilicon resin and DOPO grafting modified epoxy resin;Quick ceramming core phase is composed of chemical bonding type rare earth La and Yb co-doped siloxane ceramic precursor and boron-aluminum silicate;Synergistic reinforcing phase is composed of amino carbon nanotube, titanate modified nano Al2O3 and graphene nanosheet.The coating of the present application has the characteristics of quick ceramming, high adhesion, excellent ablation-resistant oxidation resistance and anti-cracking performance etc..
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of composite material surface protection technology, and particularly relates to a rapid ceramic coating and its preparation method. Background Technology

[0002] Carbon fiber composites, epoxy phenolic resin composites, and glass fiber composites are widely used in key components of aerospace, rail transportation, and high-end equipment due to their excellent properties of being lightweight and high-strength, such as rocket engine nozzles, high-speed rail bodies, and wing leading edges. However, these composite materials are prone to oxidation ablation and thermal degradation failure under extreme environments such as high-temperature flames, thermal shock, and oxidative corrosion, thus requiring the preparation of protective coatings on their surfaces.

[0003] Organosilicon-based ceramic coatings have attracted attention because they can be transformed into ceramic layers at high temperatures. However, the current ceramic protective coatings on the surface of composite parts have several technical bottlenecks, such as slow high-temperature ceramicization rate, weak adhesion to the substrate, easy cracking of the ceramic layer, and insufficient resistance to ablation and oxidation. In addition, traditional ceramic coatings also have problems such as poor compatibility between formulation and process. The specific defects are as follows: (1) Slow ceramicization response. The degree of ceramicization is <30% below 800℃, and it takes >30 minutes for complete ceramicization at 1000℃. The composite matrix is ​​easily oxidized and ablated in the early stage of high temperature, and cannot cope with instantaneous high-temperature thermal shock; (2) Weak bonding between coating and substrate interface. The interface shear strength is <15MPa. After high and low temperature cycling (e.g., 10 cycles of high and low temperature from -50℃ to 300℃), the coating peeling rate is >60%. The coating is easy to peel off and cannot withstand vibration, scouring and other working conditions; (3) The ceramic layer is brittle and easy to crack at high temperature. The SiO2 single crystal phase layer formed after ceramicization has poor toughness. The linear expansion coefficient does not match the composite matrix (difference >8×10). -6 / ℃), after ablation at 1200℃, the crack width of the ceramic layer is >50μm, and external oxygen and heat can easily penetrate the substrate; (4) Insufficient ablation and oxidation resistance, the ceramic phase has no dense structure, the linear ablation rate after ablation at 1000℃ oxygen-acetylene flame is >0.2mm / s, the high temperature oxidation resistance time is <60min, and the coating has poor erosion resistance and is easily eroded under high-speed airflow; (5) Poor compatibility between formulation and process, traditional coating fillers are prone to agglomeration, requiring a large amount of dispersant, resulting in poor coating film formation; and the coating process is complex, with low production efficiency and high cost.

[0004] Therefore, it is essential to provide a rapid ceramic coating for surface protection of composite materials, which exhibits rapid ceramicization, high adhesion, excellent ablation and oxidation resistance, and excellent crack resistance, as well as its preparation method. Summary of the Invention

[0005] To address one or more technical problems existing in the prior art, this invention provides a rapid ceramicization coating and its preparation method. The rapid ceramicization coating of this invention combines rapid ceramicization, high adhesion, excellent ablation and oxidation resistance, and excellent crack resistance, thus solving problems such as slow ceramicization rate, weak interfacial bonding, easy cracking of the ceramic layer, and poor ablation and oxidation resistance in existing ceramicization coatings.

[0006] The present invention provides a rapid ceramicization coating in a first aspect. The raw materials for preparing the rapid ceramicization coating include a coating composition comprising the following components by mass percentage: 35-50% graft-modified matrix material, 25-35% rapid ceramicization core phase, 9-25% synergistic reinforcing phase, 3-8% functional additives, and 12-25% mixed dispersion solvent. The graft-modified matrix material is composed of KH560 and KH570 double-grafted modified methylphenyl silicone resin and DOPO grafted modified epoxy resin in a mass ratio of (1.5-5):1. The rapid ceramicization core phase is composed of chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and borosilicate in a mass ratio of 4:(0.5-1.5). The synergistic reinforcing phase is composed of aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets.

[0007] In a second aspect, the present invention provides a method for preparing a rapid ceramic coating according to the first aspect of the present invention, the method comprising the following steps: (1) KH560 and KH570 double-grafted modified methylphenyl silicone resin was compounded with DOPO grafted modified epoxy resin to obtain grafted modified base material. (2) Aminated carbon nanotubes, titanate-modified nano-Al2O3 and graphene nanosheets were uniformly dispersed in a mixed dispersion solvent to obtain a synergistically reinforced phase dispersion. (3) The grafted modified base material, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, boroaluminosilicate, synergistic reinforcing phase dispersion and functional additives are mixed evenly to obtain a coating composition, and then the coating composition is formulated into a slurry. (4) A slurry is gradient coated on the surface of the composite matrix and cured, thereby preparing a rapid ceramic coating on the surface of the composite matrix.

[0008] In a third aspect, the present invention provides the application of a rapid ceramic coating according to the first aspect of the present invention or a rapid ceramic coating prepared by the preparation method according to the second aspect of the present invention in the surface protection of composite material parts, said composite material parts including carbon fiber composite parts, epoxy phenolic resin composite parts or glass fiber composite parts.

[0009] This invention achieves a comprehensive improvement in the rapid ceramization coating in terms of high-temperature rapid ceramization, high interfacial adhesion, low structural expansion and crack resistance, ablation and oxidation resistance, and efficient process adaptation through the synergistic effect of graft-modified matrix material, rapid ceramization core phase and synergistic reinforcing phase, and one-step slurry preparation and gradient coating process. Compared with the prior art, it has at least the following beneficial effects: (1) This invention introduces a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and boroaluminosilicate as a rapid ceramicization core phase. This rapid ceramicization core phase can coordinate with the Si-O bonds of the organosilicon resin in the grafted modified matrix, reducing the activation energy of the Si-O bonds, and causing the organosilicon resin to undergo rapid pyrolysis, oxidation, and crystallization reactions at 800℃ to generate amorphous SiO2. Furthermore, it can induce the amorphous SiO2 to transform into crystalline cristobalite, which is beneficial to the rapid ceramicization coating of this invention. The ceramicization degree of the layer is >80% at 800℃ and can be fully ceramicized within 10 minutes at 1000℃, which is conducive to achieving high-temperature instantaneous ceramicization and improves the ceramicization rate by more than 3 times compared with traditional rare earth-free catalytic coatings. At the same time, the rapid ceramicization core phase can effectively refine the ceramic grains through rare earth grain boundary segregation, improve the density of the ceramic layer, solve the problems of slow high-temperature response and protection lag of traditional ceramic coatings, and enable it to effectively cope with instantaneous high-temperature thermal shock and avoid oxidation and ablation of the composite matrix in the early stage of high temperature.

[0010] (2) This invention introduces KH560 and KH570 double-grafted modified methylphenyl silicone resin, whose -SiOH reacts with the -OH, -NH2 and other active groups on the surface of the composite matrix to form a chemically bonded organic-inorganic transition interface layer, thus achieving covalent bonding between the coating and the matrix. At the same time, DOPO grafted modified epoxy resin is introduced, whose residual epoxy groups on the molecular chain can undergo ring-opening bonding reactions with the active functional groups in the resin phase of the composite matrix. In addition, its epoxy resin segment has excellent chemical compatibility with the matrix resin phase. The two work together to enhance the interfacial bonding strength between the coating and the matrix, increasing the interfacial shear strength to over 30MPa, effectively solving the problem of coating peeling off under scouring and high and low temperature cycling conditions, and achieving ultra-high adhesion between the coating and the matrix.

[0011] (3) This invention uses aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets to form a synergistic reinforcing phase. The aminated carbon nanotubes and graphene nanosheets form a continuous three-dimensional nanoskeleton in the coating. After ceramization, this skeleton is embedded in the SiO2 ceramic layer. Through bridging, pull-out, and crack deflection effects, the toughness and density of the ceramic layer are improved synergistically, reducing the difference in the coefficient of linear expansion between the coating and the composite matrix to <3×10. -6 / ℃, to avoid high-temperature cracking of the ceramic layer; at the same time, the introduced borosilicate can decompose at high temperature to generate B2O3-SiO2-Al2O3 glass phase, which flows and solidifies in the pores of the ceramic layer, filling the pores to form a dense ceramic layer, blocking oxygen and heat intrusion, and improving the coating's ablation resistance and oxidation resistance.

[0012] (4) The preparation process of the present invention is simple, the particle size of the prepared slurry is <200nm, and no large amount of dispersing agent is required throughout the process; through the gradient coating process, the slurry with a solid content of 30~70wt% is coated 2~3 times, and a different solid content is used for each coating to form a multi-layer composite coating. Finally, the rapid ceramic coating with better performance is obtained by low temperature segmented curing. It is suitable for various processes such as brushing, spraying, and dipping, and is suitable for large-scale industrial production. It has high production efficiency and low cost. Attached Figure Description

[0013] To more clearly illustrate the technical solutions in the embodiments of the present invention, the accompanying drawings used in the description of the embodiments will be briefly introduced below. Obviously, the accompanying drawings described below are some embodiments of the present invention, and are only used to more clearly illustrate the technical solutions of the embodiments of the present invention, and should not be regarded as a limitation on the scope. For those skilled in the art, other drawings can be obtained based on these drawings without creative effort.

[0014] Figure 1 This is a flowchart illustrating the preparation process of a rapid ceramic coating in some specific embodiments of the present invention. Detailed Implementation

[0015] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below in conjunction with the embodiments thereof. Obviously, the described embodiments are only some, not all, of the embodiments of this invention. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0016] Existing ceramicized coatings are mostly physical blends of single organosilicon base materials and unmodified ceramic fillers. There is no effective bonding between the base material and the ceramic filler, or between the coating and the substrate. This results in core defects such as slow ceramicization response, weak interfacial adhesion, and easy cracking of the ceramic layer at high temperatures. Furthermore, the ceramic filler is prone to agglomeration, requiring the addition of large amounts of dispersing agents, leading to poor film formation. The coating and curing processes are complex, resulting in low production efficiency and high costs, making it difficult to meet the long-term protection requirements of composite material parts in extreme environments. Therefore, this invention provides a rapid ceramicized coating suitable for the surface protection of composite materials and its preparation method.

[0017] The present invention provides, in a first aspect, a rapid ceramization coating (abbreviated as ceramization coating), wherein the raw materials for preparing the rapid ceramization coating comprise a coating composition, the coating composition comprising the following components in weight percentage: The graft-modified matrix comprises 35-50% (e.g., 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, 46%, 47%, 48%, 49%, or 50%), the rapid ceramization core phase comprises 25-35% (e.g., 25%, 26%, 27%, 28%, 29%, 30%, 31%, 32%, 33%, 34%, or 35%), the synergistic reinforcing phase comprises 9-25% (e.g., 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%), preferably 9-15%, and the functional additive comprises 3-8% (e.g., 35%, 36%, 37%, 38%, 39%, 40%, 41%, 42%, 43%, 44%, 45%, or 50%). The grafted modified base material consists of 3%, 4%, 5%, 6%, 7%, or 8% of methylphenyl silicone resin and 12-25% (e.g., 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, or 25%) of KH560 and KH570 double-grafted modified methylphenyl silicone resin and DOPO grafted modified epoxy resin in a mass ratio of (1.5-5):1 (e.g., 1.5:1, 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, or 5:1). In the grafted modified base material, KH560 and KH570 double-grafted modified... The mass ratio of methylphenyl silicone resin to DOPO-grafted modified epoxy resin is controlled at (1.5~5):1. This facilitates the complementary advantages of the silicone and epoxy components: the silicone resin imparts excellent high-temperature resistance, flexibility, and hydrophobicity to the coating, while the epoxy resin provides high adhesion, mechanical strength, and reactivity. Within this ratio range, the two components can react with the active groups of the epoxy resin through the Si-OH group of the silicone to form a co-crosslinked network structure, enabling the rapidly ceramicized coating to possess both excellent high-temperature ceramicization properties and interfacial bonding strength. This invention has found that if the proportion of silicone resin is too high, the epoxy resin is relatively insufficient, resulting in decreased coating adhesion, reduced crosslinking density, and a tendency for cracking or peeling after film formation. If the proportion of epoxy resin is too low... If the temperature is too high, the silicone resin content will be relatively low, resulting in decreased high-temperature resistance and flexibility of the coating, insufficient ceramization transformation at high temperatures, and significantly reduced ablation resistance. In the grafted modified matrix, a covalent network is constructed by grafting silane coupling agents (KH560 and KH570) to achieve chemical bonding between the matrix and the composite matrix and ceramic phase, thereby improving interfacial adhesion. Methylphenyl silicone resin provides the Si source for ceramization, epoxy resin improves the film-forming properties and toughness of the matrix, and DOPO grafting imparts flame retardancy to the matrix. The rapid ceramization core phase consists of a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and borosilicate in a mass ratio of 4:(0.5~1.5) (e.g., 4:0.5, 4:1, or 4:1).5) Composition; In the rapidly ceramicizing core phase, rare earth La and Yb co-doping can act as ceramicizing catalysts, reducing the activation energy of organosilicon resin ceramicizing and achieving a ceramicizing degree >80% at 800℃ and complete ceramicizing within 10 minutes of pyrolysis at 1000℃; boroaluminosilicate can decompose at high temperature to generate a B2O3-SiO2-Al2O3 glass phase, filling the pores of the ceramic layer and achieving ceramic layer densification; In the rapidly ceramicizing core phase, the mass ratio of chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor to boroaluminosilicate is controlled at 4:(0.5~1.5), which can realize the combined function of both. This invention achieves complementary and synergistic effects by discovering that chemically bonded rare-earth La and Yb co-doped siloxane ceramic precursors decompose at high temperatures to transform into a dense SiO2-based ceramic framework, providing the main structure and high-temperature strength of the coating. The B2O3-SiO2-Al2O3 eutectic glass phase generated by the decomposition of borosilicate flows and solidifies in the pores of the ceramic layer, filling micropores and cracks to form a dense anti-oxidation layer. When the proportion of borosilicate is too low, insufficient B2O3-SiO2-Al2O3 glass phase is generated, the pores of the ceramic layer cannot be effectively filled, the coating density decreases, and oxidizing atmospheres easily penetrate the interior. When the proportion of borosilicate is too low, the formation of the B2O3-SiO2-Al2O3 glass phase is insufficient, the pores of the ceramic layer cannot be effectively filled, the coating density decreases, and oxidizing atmospheres easily penetrate the interior. When the salt ratio is too high, the excess of the B2O3-SiO2-Al2O3 glass phase will lower the high-temperature softening point of the ceramic layer, making it prone to melting and loss at ultra-high temperatures, thus weakening the coating's ablation resistance. The synergistic reinforcing phase consists of aminated carbon nanotubes, titanate-modified nano-Al2O3 (i.e., titanate-modified nano-alumina), and graphene nanosheets. This invention does not specifically limit the aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets; they can be directly purchased products or products prepared by existing methods. In this invention, the aminated carbon nanotubes (e.g., aminated...) The multi-walled carbon nanotubes have a diameter of, for example, 10-20 nm and a length of, for example, 5-20 μm; the titanate-modified nano-Al₂O₃ has a particle size of, for example, 50-80 nm, and the graphene nanosheets have, for example, 5-10 layers; in the synergistic reinforcing phase used, aminated carbon nanotubes and graphene nanosheets can construct a three-dimensional nanoskeleton, improving the toughness and crack resistance of the ceramic layer and matching the coefficients of linear expansion of the coating and the substrate; the titanate-modified nano-Al₂O₃ can transform from the γ phase to α-Al₂O₃ (corundum phase) at high temperatures, significantly improving the hardness and high-speed erosion resistance of the ceramic layer.

[0018] This invention introduces grafted modified matrix material, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, boroaluminosilicate, and synergistic reinforcing phase into the coating composition, so that the ceramicized coating has the advantages of rapid ceramicization, high adhesion, and crack resistance. At the same time, it optimizes the high temperature ablation resistance, oxidation resistance, and erosion resistance of the ceramicized coating, and achieves the matching of the linear expansion coefficient between the ceramicized coating and the composite matrix. Specifically, this invention introduces a chemically bonded rare-earth La and Yb co-doped siloxane ceramic precursor and boroaluminosilicate as a rapid ceramicization core phase. This rapid ceramicization core phase can coordinate with the Si-O bonds of the organosilicon resin in the grafted modified matrix, reducing the activation energy of the Si-O bonds. This allows the organosilicon resin to undergo rapid pyrolysis, oxidation, and crystallization reactions at 800℃, generating amorphous SiO2. Furthermore, it can induce the amorphous SiO2 to transform into crystalline cristobalite. This is beneficial for achieving a ceramicization degree of >80% at 800℃ in the rapid ceramicization coating of this invention, and complete ceramicization within 10 minutes at 1000℃. This facilitates high-temperature instantaneous ceramicization, increasing the ceramicization rate by more than 3 times compared to traditional rare-earth-free catalytic coatings. At the same time, this rapid ceramicization core phase can effectively refine ceramic grains through rare-earth grain boundary segregation, improving the density of the ceramic layer and solving the problems of slow high-temperature response and delayed protection in traditional ceramicization coatings. This enables it to effectively cope with instantaneous high-temperature thermal shock and avoid oxidation and ablation of the composite matrix in the early stage of high temperature. This invention introduces KH560 and KH570 double-grafted modified methylphenyl silicone resin. Its -SiOH groups undergo dehydration condensation with active groups such as -OH and -NH2 on the surface of the composite matrix, forming a chemically bonded organic-inorganic transition interface layer, achieving covalent bonding between the coating and the matrix. Simultaneously, DOPO grafted modified epoxy resin is introduced. The residual epoxy groups on its molecular chain can undergo ring-opening bonding with the active functional groups in the resin phase of the composite matrix, and its epoxy resin segment exhibits excellent chemical compatibility with the matrix resin phase. These two components synergistically enhance the interfacial bonding strength between the coating and the matrix, increasing the interfacial shear strength to over 30 MPa, effectively solving the problem of coating peeling and detachment under scouring and high / low temperature cycling conditions, and achieving ultra-high adhesion between the coating and the matrix. This invention utilizes aminated carbon nanotubes, titanate-modified nano-Al₂O₃, and graphene nanosheets to form a synergistic reinforcing phase. The aminated carbon nanotubes and graphene nanosheets form a continuous three-dimensional nanoskeleton within the coating. After ceramization, this skeleton is embedded in the SiO₂ ceramic layer. Through bridging, pull-out, and crack deflection effects, the toughness and density of the ceramic layer are synergistically improved, reducing the difference in linear expansion coefficients between the coating and the composite matrix to <3×10⁻⁶. -6The temperature is / ℃, avoiding high-temperature cracking of the ceramic layer; simultaneously, the introduced borosilicate can decompose at high temperature to generate B2O3-SiO2-Al2O3 glass phase, which flows and solidifies in the pores of the ceramic layer, filling the pores to form a dense ceramic layer, blocking oxygen and heat intrusion, and improving the coating's ablation resistance and oxidation resistance. The preparation process of this invention is simple, the particle size in the prepared slurry is <200nm, and no large amount of dispersing additives are required throughout the process; through a gradient coating process, that is, using a slurry with a solid content increasing sequentially in the range of 30~70wt% for 2~3 coatings, each coating using a slurry with a different solid content, a multi-layer composite coating is formed, and finally, a high-performance rapid ceramic coating is obtained by low-temperature segmented curing, which is suitable for various processes such as brushing, spraying, and dip coating, and is suitable for large-scale industrial production, with high production efficiency and low cost. In addition, the coating formulation of this invention can be precisely fine-tuned according to the performance requirements of different application scenarios, and is suitable for surface protection of various composite materials such as carbon fiber, epoxy phenolic resin, and glass fiber, with a wide range of applications and strong industrial application value.

[0019] According to some preferred embodiments, the raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560 (i.e., γ-glycidoxypropyltrimethoxysilane), KH570 (i.e., γ-methacryloyloxypropyltrimethoxysilane), and hydroxyl-terminated methylphenyl silicone resin. The mass ratio of KH560 to KH570 is 2:(0.5~1.5) (e.g., 2:0.5, 2:1, or 2:1.5), and the sum of the mass amounts of KH560 and KH570 is 5~10% (e.g., 5%, 6%, 7%, 8%, 9%) of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. Or 10%); and / or the raw materials for preparing the DOPO graft-modified epoxy resin include 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO and epoxy resin, wherein the mass amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO is 10~22.5% of the mass amount of epoxy resin (e.g., 10%, 12.5%, 15%, 17.5%, 20% or 22.5%); in the graft-modified base material, the mass ratio of KH560 to KH570 is preferably controlled at 2:(0.5~1.5), and the total mass amount of both is hydroxyl-terminated methylphenyl silicone resin. Using 5-10% by mass can achieve moderate grafting modification of the silicone resin surface. KH560 provides epoxy group reaction sites to enhance chemical bonding with epoxy resin, while KH570 provides double bonds to regulate polarity and crosslinking density. The synergy of these two components is beneficial for achieving optimal interfacial compatibility between silicone and epoxy resins, a uniform crosslinking network, and moderate polarity. This invention has found that if the mass ratio of KH560 to KH570 deviates from the specified range, such as insufficient KH570 leading to insufficient crosslinking sites and weak interfacial bonding, or excessive KH570 leading to excessively high polarity and decreased system compatibility, and insufficient total mass of both resulting in insufficient grafting rate and poor interfacial bonding, then… Excessive total mass of both will lead to overgrafting, resulting in excessively high system viscosity and uneven crosslinking, both of which will reduce the coating's density and crack resistance. In DOPO-grafted modified epoxy resin, the preferred DOPO mass content is controlled at 10-22.5% of the epoxy resin mass. This can introduce an appropriate amount of phosphaphenanthrene structure into the epoxy resin, giving it good flame retardancy and charring properties, while maintaining the mechanical strength and adhesion of the epoxy resin. If the DOPO content is too low, the flame retardant effect will be insignificant; if it is too high, the excessive phosphaphenanthrene structure will lead to a decrease in the crosslinking density of the epoxy resin, an increase in coating brittleness, and a decrease in adhesion, thereby affecting the overall ablation resistance and mechanical stability of the coating.

[0020] According to some preferred embodiments, the raw materials for preparing the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor include a siloxane ceramic precursor, lanthanum nitrate (e.g., lanthanum nitrate hexahydrate), and ytterbium nitrate (e.g., ytterbium nitrate pentahydrate). The sum of the mass amounts of lanthanum nitrate and ytterbium nitrate is 1.5-2.8% (e.g., 1.5%, 2%, 2.5%, or 2.8%) of the siloxane ceramic precursor, and the mass ratio of lanthanum nitrate to ytterbium nitrate is 4:(0.5-1.6) (e.g., 4:0.5, 4:1, or 4:1.6). In this invention, preferably, the sum of the mass amounts of lanthanum nitrate and ytterbium nitrate is 1.5-2.8% of the mass of the siloxane ceramic precursor, and the mass ratio of lanthanum nitrate to ytterbium nitrate is controlled at 4:(0.5-1.6). This invention achieves a synergistic catalytic effect of rare earth elements. La (lanthanum) can promote the cracking and rearrangement of ceramic precursors, improving the ceramicization conversion rate; Yb (ytterbium) can enhance the high-temperature stability and oxidation resistance of the ceramic layer. Co-doping of both can regulate the ceramic microstructure, inhibit high-temperature grain coarsening, and promote the formation of a continuous and dense protective layer. This invention found that if the total doping amount of La and Yb is too low, the rare earth catalytic effect is insufficient, the ceramicization transformation is incomplete, and the high-temperature strength and oxidation resistance of the coating will decrease. If the total doping amount of La and Yb is too high, the excessive rare earth elements will form a second phase segregation in the ceramic layer, destroying the uniformity of the ceramic structure, which will lead to increased brittleness and reduced thermal shock resistance of the coating. All of these will weaken the synergistic effect of co-doping and affect the long-term protective performance of the coating under extreme high-temperature environments.

[0021] According to some preferred embodiments, the boron aluminum silicate contains 3-5% boron by mass (e.g., 3%, 4%, or 5%). In this invention, the boron aluminum silicate can be, for example, boron aluminum silicate glass powder. This invention does not specifically limit the boron aluminum silicate glass powder, and those skilled in the art can conventionally select it. For example, it is preferable to use boron aluminum silicate glass powder with a boron by mass content of 3-5%. It can be a product that can be purchased directly or a product prepared by existing methods. In this invention, the particle size D50 of the boron aluminum silicate glass powder can be, for example, 5-20 μm.

[0022] According to some preferred embodiments, in the synergistic reinforcing phase, the mass ratio of aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets is (1.8~2.2):(2.5~3.5):1, preferably 2:3:1. In the synergistic reinforcing phase, titanate-modified nano-Al2O3 is added. This invention has found that titanate modification can significantly improve the interfacial compatibility between nano-Al2O3 and the organosilicon resin matrix. By forming a coating layer on the surface of the nano-Al2O3 particles with titanate, the surface energy of the nano-Al2O3 is reduced, effectively inhibiting its aggregation and ensuring uniform dispersion in the system. Furthermore, the titanate-modified nano-Al2O3 serves as a rigid... Inorganic particles can act as physical cross-linking points in the coating, improving its mechanical strength, hardness, and wear resistance. More importantly, nano-Al2O3 can react with SiO2 produced by the decomposition of ceramic precursors at high temperatures to form mullite or aluminosilicate glass phases, which is beneficial for enhancing the structural density and high-temperature stability of the ceramic layer. In this invention, the preferred mass ratio of aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets is (1.8~2.2):(2.5~3.5):1. Aminated carbon nanotubes and graphene nanosheets can construct a three-dimensional network structure, forming effective stress transfer and crack deflection paths in the coating, significantly improving the coating's performance. Cracking resistance and fracture toughness: Titanate-modified nano-Al2O3 acts as a rigid framework filling the pores of the carbon nanotube / graphene three-dimensional network, playing a role in particle reinforcement and interface pinning. The three components work synergistically to form a "point-line-surface" multidimensional reinforcement network. Within this preferred ratio range, the three components can form the best synergistic reinforcement effect. When the ratio of aminated carbon nanotubes to graphene nanosheets is moderate, the carbon materials interpenetrate and disperse synergistically, avoiding their own agglomeration. The content of titanate-modified nano-Al2O3 is appropriate, which can provide sufficient rigidity reinforcement without increasing the brittleness of the coating due to excessive amount. This invention found that if the ratio of aminated carbon nanotubes and / or graphene nanosheets is too high, the carbon materials are prone to cracking. Agglomeration leads to increased local defects and uneven mechanical properties in the coating. Insufficient rigid inorganic framework reduces the coating's hardness and wear resistance. If the proportion of titanate-modified nano-Al2O3 is too high, excessive rigid inorganic particles will destroy the three-dimensional network structure constructed by carbon nanotubes / graphene, resulting in increased coating brittleness and decreased flexibility. Furthermore, excessive inorganic phase may cause the ceramic layer to crack during high-temperature ceramization. When the ratio of aminated carbon nanotubes to graphene nanosheets is unbalanced, insufficient aminated carbon nanotubes result in insufficient one-dimensional bridging, while insufficient graphene nanosheets weaken the two-dimensional barrier and lubrication effects. The two cannot form an effective three-dimensional network, and the coating's crack resistance and ablation resistance will both decrease.

[0023] According to some preferred embodiments, the functional additives include a coupling agent, a curing agent, a leveling agent, and an anti-settling agent, wherein the mass ratio of the coupling agent, curing agent, leveling agent, and anti-settling agent is (1~3):(1~2):(0.3~1):(0.5~2). In this invention, the coupling agent may be, for example, KH550 (i.e., γ-aminopropyltriethoxysilane) and / or KH560. When the coupling agent is composed of KH550 and KH560, the mass ratio of KH550 to KH560 is, for example, 1:2. The curing agent may be, for example, diethylenetriamine DETA. The leveling agent may be, for example, a polyether-modified polysiloxane leveling agent, such as BYK-333. The anti-settling agent may be, for example, fumed silica and / or silica. The main function of these functional additives is to improve the coating's dispersibility, film-forming properties, and anti-settling properties, promote low-temperature curing of the coating, and prevent the agglomeration of ceramic fillers.

[0024] According to some preferred embodiments, the grafted modified base material further contains dibutyl phthalate plasticizer, and the mass amount of the dibutyl phthalate plasticizer is, for example, 3 to 6% of the mass of the KH560 and KH570 double-grafted modified methylphenyl silicone resin.

[0025] According to some preferred embodiments, the mixed dispersion solvent is composed of anhydrous ethanol and ethyl acetate; in some specific embodiments, the mixed dispersion solvent is, for example, composed of anhydrous ethanol and ethyl acetate in a mass ratio of 3:(1.5~2.8), which can adjust the solid content and viscosity of the coating composition and is suitable for various coating processes such as brushing, spraying, and dipping.

[0026] In a second aspect, the present invention provides a method for preparing the rapid ceramic coating described in the first aspect, the method comprising the following steps: (1) KH560 and KH570 double-grafted modified methylphenyl silicone resin was compounded with DOPO grafted modified epoxy resin to obtain grafted modified base material. (2) Aminated carbon nanotubes, titanate-modified nano-Al2O3 and graphene nanosheets were uniformly dispersed in a mixed dispersion solvent to obtain a synergistically reinforced phase dispersion. (3) The grafted modified base material, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, boroaluminosilicate, synergistic reinforcing phase dispersion and functional additives are mixed evenly to obtain a coating composition, and then the coating composition is formulated into a slurry; In this invention, for example, a mixed dispersion solvent composed of anhydrous ethanol and ethyl acetate in a mass ratio of 3:(1.5~2.5) is used to formulate the coating composition into slurries with different solid contents; (4) A slurry is gradient coated on the surface of the composite matrix and cured, thereby preparing a rapid ceramic coating on the surface of the composite matrix.

[0027] The method of the present invention simplifies the preparation and coating process of the rapid ceramic coating, reduces the amount of dispersant used, improves the film-forming properties and application compatibility of the coating, and enables low-cost, large-scale preparation to meet the surface protection needs of different composite material parts.

[0028] According to some preferred embodiments, the gradient coating involves applying 2-3 coats of a slurry with a solid content increasing sequentially within the range of 30-70 wt%. In this invention, the solid content refers to the sum of the mass percentages of the grafted modified matrix, the rapidly ceramicized core phase, the synergistic reinforcing phase, and the functional additives contained in the slurry; the mixed dispersion solvent is not included in the solid content. Preferably, this invention uses a slurry with a solid content increasing sequentially within the range of 30-70 wt% for 2-3 gradient coatings. Compared to a single coating, although the solid components of each coating layer are the same, the gradient change in solid content is achieved only by adjusting the amount of mixed dispersion solvent. However, this simple process adjustment can bring about a functional synergistic effect in the multilayer structure. The base coat (which directly contacts the surface of the composite matrix) uses, for example, a low-solid-content (30-40 wt%) slurry with low viscosity and good fluidity, which can... The coating fully wets the surface of the composite matrix and penetrates into the micropores. After curing, it forms an interfacial transition layer, which has a dual effect of mechanical interlocking and chemical bonding with the composite matrix, significantly improving the coating adhesion. The intermediate layer, for example, uses a medium solid content (40~60wt%) slurry to form a load-bearing layer with a certain thickness, which plays a role in stress buffering and structural transition. The topcoat layer, for example, uses a high solid content (60~70wt%) slurry. After curing, the filler packing density is high, and it rapidly ceramizes at high temperature to form a dense antioxidant protective layer. This can effectively alleviate the coating curing shrinkage stress and thermal mismatch stress during high-temperature service, and prevent the coating from cracking or peeling. Compared with single coating, the gradient coating method used in this invention achieves synergistic optimization of coating adhesion, crack resistance and ablation resistance by controlling the solid content gradient without changing the coating composition.

[0029] According to some preferred embodiments, the curing is low-temperature segmented curing, which includes 2 to 3 stages of temperature-increasing curing, with the curing temperature increasing sequentially within the range of 60 to 120°C, and the total curing time being 2 to 5 hours.

[0030] According to some preferred embodiments, the preparation of the KH560 and KH570 double-grafted modified methylphenyl silicone resin includes: heating hydroxyl-terminated methylphenyl silicone resin to 85-100°C to melt it, then uniformly spraying an aqueous acetic acid solution with a pH of 4-5 onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activating it at 85-100°C for 20-40 min to obtain a modified resin with a surface rich in silanol groups (Si-OH); preparing a silane coupling agent solution by using an aqueous ethanol solution to KH560 and KH570, then adjusting the pH of the silane coupling agent solution to 4-5 and pre-hydrolyzing it for 20-60 min to obtain a pre-hydrolyzed silane coupling agent solution; mixing the modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate evenly and reacting them at 85-100°C and a rotation speed of 300-500 r / min for 3-3.5 h, followed by cooling and vacuum degassing to obtain KH560. The invention comprises a methylphenyl silicone resin modified by double grafting of KH560 and KH570. In this invention, the ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is, for example, (10~20) mL:100g. The ethanol aqueous solution is prepared by mixing anhydrous ethanol and water at a volume ratio of (8~10):1. The silane coupling agent solution contains 1~5% by mass of KH560 and KH570. Dibutyltin dilaurate is used as a catalyst, and the amount of dibutyltin dilaurate is, for example, 0.02~0.05% of the mass of the hydroxyl-terminated methylphenyl silicone resin. In this invention, the hydroxyl-terminated methylphenyl silicone resin refers to hydroxyl-terminated polymethylphenylsiloxane. This invention does not specifically limit the hydroxyl-terminated methylphenyl silicone resin; those skilled in the art can conventionally select commercially available hydroxyl-terminated methylphenyl silicone resin (i.e., commercially available hydroxyl-terminated polymethylphenylsiloxane).

[0031] According to some preferred embodiments, the preparation of the DOPO graft-modified epoxy resin includes: preheating the epoxy resin, then adding a solution of N-methylpyrrolidone (NMP) of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) dropwise into the preheated epoxy resin, then adding triphenylphosphine and reacting under inert gas protection at a temperature of 130-150°C and a rotation speed of 400-600 r / min for 3-6 h, followed by vacuum distillation and degassing to obtain the DOPO graft-modified epoxy resin. The epoxy resin; in this invention, nitrogen and / or argon are used for inert gas protection, and the N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide (DOPO) contains, for example, 20-30% by mass of DOPO; the epoxy resin can be, for example, epoxy resin E51 and / or epoxy resin E44; in this invention, triphenylphosphine is used as a catalyst, and the amount of triphenylphosphine used is, for example, 0.05-0.15% by mass of the epoxy resin.

[0032] According to some preferred embodiments, the preparation of the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor in anhydrous ethanol, then adding water (e.g., deionized water), lanthanum nitrate (e.g., lanthanum nitrate hexahydrate), and ytterbium nitrate (e.g., ytterbium nitrate pentahydrate), and ultrasonically dispersing at 20-40°C for 20-40 min to obtain the precursor system; then adjusting the pH of the precursor system to 2-3 to carry out a sol-gel reaction; then heating to 70-75°C and stirring for 1-3 h; finally, undergoing vacuum distillation and vacuum degassing to obtain the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor. Yb co-doped siloxane ceramic precursor; in this invention, the siloxane ceramic precursor is, for example, a polysiloxane (e.g., methyl silicone resin and / or methylphenyl silicone resin); the mass ratio of the siloxane ceramic precursor, anhydrous ethanol, and water is, for example, 1:(0.5~1.5):(0.1~0.3), and the pH of the precursor system is adjusted to 2~3, for example, by adding dilute nitric acid and / or acetic acid; the temperature of the sol-gel reaction is, for example, 20~40°C, and the time is, for example, 30~60 min; this invention does not specifically limit the vacuum distillation and vacuum degassing involved, which can be conventionally selected by those skilled in the art.

[0033] In a third aspect, this invention provides the application of the rapid ceramization coating described in the first aspect of the invention, or the rapid ceramization coating prepared by the preparation method described in the second aspect of the invention, in the surface protection of composite material parts, including carbon fiber composite parts, epoxy phenolic resin composite parts, or glass fiber composite parts. The rapid ceramization coating of this invention is suitable for surface protection of components made of carbon fiber composites, epoxy phenolic resin composites, or glass fiber composites, such as key components like rocket engine composite nozzles, high-speed rail composite car bodies, and aerospace composite wing leading edges.

[0034] The present invention will be further described below by way of examples, but the scope of protection of the present invention is not limited to these embodiments. The present invention may have many other embodiments, and those skilled in the art can make various corresponding changes and modifications based on the present invention without departing from its spirit and essence. However, all such corresponding changes and modifications should fall within the scope of protection of the appended claims. Unless otherwise specified, the experimental methods used in the following embodiments are conventional methods. Unless otherwise specified, the materials, reagents, etc., used in the following embodiments can be obtained commercially or by existing methods.

[0035] Example 1 This embodiment provides a rapid ceramic coating suitable for the surface protection of epoxy phenolic resin composite nozzles of rocket engines and its preparation method.

[0036] The raw materials for preparing the rapid ceramic coating in this embodiment include a coating composition designed for the extreme high-temperature ablation requirements of epoxy phenolic resin composite nozzles in rocket engines. The formulation is as follows: The grafted modified matrix is ​​obtained by mixing 350g of KH560 and KH570 double-grafted modified methylphenyl silicone resin with 100g of DOPO grafted modified epoxy resin and stirring for 1h at 400r / min and 60℃; the rapid ceramicization core phase is composed of 245g of chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and 60g of boron aluminosilicate glass powder (the boron aluminosilicate glass powder has a boron mass percentage of 4%); the synergistic reinforcing phase is composed of 40g of aminated carbon nanotubes, 60g of titanate modified nano-Al2O3 and 20g of graphene nanosheets; the functional additives are composed of 10g of KH550, 15g of diethylenetriamine, 5g of leveling agent BYK-333 and 10g of fumed silica; the mixed dispersion solvent is composed of 120g of anhydrous ethanol and 80g of ethyl acetate.

[0037] The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin. The mass ratio of KH560 to KH570 is 2:1, and the sum of the mass amounts of KH560 and KH570 is 8.57% of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. The preparation method is as follows: the hydroxyl-terminated methylphenyl silicone resin is heated to 90°C to melt, and then an acetic acid aqueous solution with a pH of 4.5 is uniformly sprayed onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activated at 90°C for 30 minutes to obtain a modified resin with a surface rich in silanol groups. The mass ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is 15 mL: 100 g. An ethanol aqueous solution (the ethanol aqueous solution is composed of anhydrous ethanol and water in a specific ratio) is used. A silane coupling agent solution was prepared by mixing KH560 and KH570 in a product ratio of 9:1 (the total mass percentage of KH560 and KH570 in the silane coupling agent solution was 3%). Then, acetic acid was added to adjust the pH of the silane coupling agent solution to 4.5 and pre-hydrolyzed for 40 min to obtain a pre-hydrolyzed silane coupling agent solution. The modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate (the amount of dibutyltin dilaurate catalyst was 0.028% of the mass of the hydroxyl-terminated methylphenyl organosilicon resin) were mixed evenly and reacted at a speed of 400 r / min and a temperature of 90℃ for 3 h. After cooling to 60℃, vacuum degassing (vacuum degree of vacuum degassing -0.09 MPa) was performed for 30 min to obtain KH560 and KH570 double-grafted modified methylphenyl organosilicon resin, which was sealed for later use.

[0038] The preparation of the DOPO graft-modified epoxy resin includes: preheating E51 epoxy resin at 70°C for 1 hour; dissolving 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone (the mass ratio of DOPO to N-methylpyrrolidone is 25:75) to obtain an N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO; and dissolving the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone. The N-methylpyrrolidone solution of DOPO (containing 15% of the mass of E51 epoxy resin) was slowly added dropwise (at a rate of 1 mL / min) to preheated E51 epoxy resin. Then, 0.1% of the mass of E51 epoxy resin of triphenylphosphine catalyst was added. The mixture was heated to 140 °C and stirred for 4 h under nitrogen protection at a speed of 500 r / min. After vacuum distillation and vacuum degassing (vacuum degree of degassing: -0.09 MPa) for 20 min, DOPO-grafted modified epoxy resin was obtained and sealed for later use.

[0039] The preparation of the chemically bonded rare-earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor (methylphenyl silicone resin) in anhydrous ethanol, then adding water (deionized water), lanthanum nitrate hexahydrate, and ytterbium nitrate pentahydrate (the mass ratio of lanthanum nitrate hexahydrate to ytterbium nitrate pentahydrate is 4:1, and the total amount of lanthanum nitrate hexahydrate and ytterbium nitrate pentahydrate is 2% of the mass of the siloxane ceramic precursor), and ultrasonically dispersing at 25°C for 30 min to obtain the precursor system. Then, acetic acid was added to adjust the pH of the precursor system to 2.8, and a sol-gel reaction was carried out at 25°C for 40 min. The temperature was then raised to 70°C and stirred at 300 r / min for 2 h. Finally, the system was subjected to vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing: -0.09 MPa) for 20 min to obtain a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor. The mass ratio of the siloxane ceramic precursor, anhydrous ethanol, and water was 1:1.2:0.2.

[0040] The preparation of the titanate-modified nano-Al2O3 is as follows: 100g of nano-Al2O3 (particle size 50~80nm) is placed in a vacuum drying oven at 120℃ and dried for 2h to remove surface adsorbed water. 100g of the dried nano-Al2O3 is weighed and added to 500mL of anhydrous ethanol, and ultrasonically dispersed for 30min to obtain a uniform nano-Al2O3 suspension. The titanate coupling agent (isopropyltris(dioctylpyrophosphoryloxy)titanate) is dissolved in anhydrous ethanol, and the amount of titanate coupling agent is 4% of the mass of nano-Al2O3, to prepare a 10% titanate coupling agent ethanol solution. Under stirring conditions (500r / min), the titanate coupling agent ethanol solution is slowly added dropwise (dropping rate 1mL / min) to the nano-Al2O3 suspension. After the addition is complete, the temperature is raised to 80℃ and the reaction is stirred at a constant temperature for 2h. After the reaction was completed, the mixture was filtered under reduced pressure. The filter cake was washed three times with anhydrous ethanol to remove unreacted titanate coupling agent. Then, the filter cake was dried in a vacuum drying oven at 80°C for 12 hours, ground and sieved to obtain titanate-modified nano-Al2O3, which was then sealed for later use.

[0041] The preparation of the rapid ceramic coating in this embodiment is as follows: Figure 1 As shown, it includes the following steps: ① Mix 120g of anhydrous ethanol and 80g of ethyl acetate to obtain a mixed dispersion solvent. Add 40g of aminated carbon nanotubes, 60g of titanate-modified nano-Al2O3, and 20g of graphene nanosheets to the mixed solvent and ultrasonically disperse for 40min at an ultrasonic power of 800W to obtain a synergistically reinforced phase dispersion.

[0042] ② The grafted modified base material, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, and borosilicate glass powder were stirred for 30 min at 60℃ and 300 r / min. Then, the synergistic reinforcing phase dispersion, 10 g of KH550, 15 g of diethylenetriamine, 5 g of BYK-333 leveling agent, and 10 g of fumed silica were added and stirred for 1 h at 60℃ and 300 r / min. Then, the mixture was ultrasonically dispersed for 30 min at an ultrasonic power of 800 W. Finally, the mixture was degassed under vacuum (vacuum degree of degassed -0.09 MPa) for 30 min to obtain the coating composition.

[0043] ③ The surface of the rocket engine epoxy phenolic resin-based composite nozzle substrate was sanded with 400-grit sandpaper, wiped with anhydrous ethanol to remove oil, vacuum dried at 80℃ for 1 hour, and then cooled to room temperature. Gradient coating was performed using a high-pressure spraying process (spraying pressure 15MPa): the coating composition obtained in steps ① and ② was diluted to slurries with solid contents of 30wt%, 50wt%, and 60wt% respectively using a mixed dispersion solvent composed of anhydrous ethanol and ethyl acetate at a mass ratio of 3:2. The slurries with solid contents of 30wt%, 50wt%, and 60wt% were then sprayed sequentially onto the surface of the rocket engine epoxy phenolic resin-based composite nozzle substrate to form an inner layer (base coat) with a thickness of 20μm, an intermediate layer with a thickness of 80μm, and an outer layer (top coat) with a thickness of 50μm. After each layer was sprayed, it was leveled at room temperature (leveling for 10 minutes for the inner layer, and 15 minutes each for the intermediate and outer layers), resulting in a coated substrate with a total coating thickness of 150μm.

[0044] ④ Place the coated substrate in an oven and cure it according to the following procedure: first, keep it at 60℃ for 2 hours, then raise the temperature to 100℃ at a rate of 2℃ / min and keep it at 1 hour, then raise the temperature to 120℃ at a rate of 2℃ / min and keep it at 1 hour. During the entire curing process, the curing pressure is 0.8MPa. After curing, allow it to cool naturally to room temperature. Thus, a rapid ceramic coating is prepared on the surface of the epoxy phenolic resin-based composite nozzle substrate of a rocket engine.

[0045] In this embodiment, the performance of the rapidly ceramicized coating was tested, and the results are shown in Table 1 below.

[0046] Table 1 In this invention, the interfacial shear strength (IFSS) was tested according to ASTM D1002-2010, the linear ablation rate according to GJB 323A-96, and the pencil hardness according to GB / T 6739-2022. In Table 1, the coating peel rate was determined as follows: the sample coated with the rapid ceramization coating was placed in a high-low temperature alternating test chamber, heated to 300℃ at a heating rate of 5℃ / min and held for 30 min, then cooled to -50℃ at a cooling rate of 10℃ / min and held for 30 min, and this cycle was repeated 50 times. After removing the sample, the percentage of the peeled area to the total coating area was measured. In Table 1, the oxidation resistance time of the coating in a static air atmosphere at 1000℃ refers to the quantitative determination of the oxidation weight gain per unit area of ​​the sample coated with the rapid ceramization coating under a static air atmosphere at 1000℃. When the cumulative oxidation weight gain per unit area of ​​the coating-substrate sample reaches 10 mg / cm³, the oxidation resistance time is determined. 2When the coating peels off or penetrates through cracks on the sample surface during the test, it is considered to have failed to resist oxidation, regardless of the weight gain. According to this criterion, the oxidation resistance time of the rapid ceramic coating of Example 1 of the present invention is 150 min in a static air atmosphere at 1000℃.

[0047] The formulation in this embodiment is adapted to the extreme ablation environment of rocket engine nozzles, achieving ultra-fast ceramization and an ultra-low linear ablation rate, with performance far superior to traditional ceramization coatings. The rapid ceramization coating in this embodiment exhibits significantly improved adhesion to the substrate, with a measured interfacial shear strength of 38 MPa. No significant peeling occurs after high and low temperature cycling, demonstrating excellent ablation and oxidation resistance. It fully meets the protection requirements of extreme aerospace environments, can replace existing zirconium-based protective coatings, and has a lower overall cost.

[0048] Example 2 This embodiment provides a rapid ceramic coating for the surface protection of high-speed railway carbon fiber composite vehicle bodies and its preparation method.

[0049] The raw materials for preparing the rapid ceramic coating in this embodiment include a coating composition. This coating composition is designed to meet the weather resistance, impact resistance, and protection in normal temperature ranges required for high-speed rail carbon fiber composite vehicle bodies. The formula is as follows: The grafted modified matrix is ​​obtained by mixing 250g of KH560 and KH570 double-grafted modified methylphenyl silicone resin, 150g of DOPO grafted modified epoxy resin, and 10g of dibutyl phthalate plasticizer, and stirring at 400r / min and 60℃ for 1h; the rapid ceramicization core phase is composed of 180g of chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and borosilicate glass powder. (The boron in the boron aluminosilicate glass powder is 4% by mass) 45g; the synergistic reinforcing phase is composed of 30g of aminated carbon nanotubes, 45g of titanate-modified nano-Al2O3 and 15g of graphene nanosheets; the functional additives are composed of 8g of KH550, 12g of diethylenetriamine, 7g of leveling agent BYK-333 and 8g of fumed silica; the mixed dispersion solvent is composed of 100g of anhydrous ethanol and 80g of ethyl acetate.

[0050] The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin. The mass ratio of KH560 to KH570 is 1.5:1, and the sum of the mass amounts of KH560 and KH570 is 10% of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. The preparation method is as follows: the hydroxyl-terminated methylphenyl silicone resin is heated to 90°C to melt, and then an acetic acid aqueous solution with a pH of 4.5 is uniformly sprayed onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activated at 90°C for 30 minutes to obtain a modified resin with a surface rich in silanol groups. The mass ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is 15 mL: 100 g. An ethanol aqueous solution (the ethanol aqueous solution is composed of anhydrous ethanol and water in a certain proportion) is used. A silane coupling agent solution was prepared by mixing KH560 and KH570 in a volume ratio of 9:1 (the total mass percentage of KH560 and KH570 in the silane coupling agent solution was 3%). Then, acetic acid was added to adjust the pH of the silane coupling agent solution to 4.5 and pre-hydrolyzed for 40 min to obtain a pre-hydrolyzed silane coupling agent solution. The modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate (the amount of dibutyltin dilaurate catalyst was 0.04% of the mass of the hydroxyl-terminated methylphenyl organosilicon resin) were mixed evenly and reacted at a speed of 400 r / min and a temperature of 90℃ for 3 h. After cooling to 60℃, vacuum degassing (vacuum degree of vacuum degassing -0.09 MPa) was performed for 30 min to obtain KH560 and KH570 double-grafted modified methylphenyl organosilicon resin, which was sealed for later use.

[0051] The preparation of the DOPO graft-modified epoxy resin includes: preheating E44 epoxy resin at 70°C for 1 hour; dissolving 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone (the ratio of DOPO to N-methylpyrrolidone is 25:75) to obtain an N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO; and dissolving the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone. The N-methylpyrrolidone solution of DOPO (containing 10% of the mass of E44 epoxy resin) was slowly added dropwise (1 mL / min) to preheated E44 epoxy resin. Then, 0.067% of the mass of E44 epoxy resin of triphenylphosphine catalyst was added. The mixture was heated to 140 °C and stirred for 4 h under nitrogen protection at a speed of 500 r / min. After vacuum distillation and vacuum degassing (vacuum degree of degassing: -0.09 MPa) for 20 min, DOPO-grafted modified epoxy resin was obtained and sealed for later use.

[0052] The preparation of the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor (methylphenyl silicone resin) in anhydrous ethanol, then adding water (deionized water), lanthanum nitrate hexahydrate, and ytterbium nitrate pentahydrate (the mass ratio of lanthanum nitrate hexahydrate to ytterbium nitrate pentahydrate is 3:1, and the total amount of lanthanum nitrate hexahydrate and ytterbium nitrate pentahydrate is 2.22% of the mass of the siloxane ceramic precursor), and ultrasonically dispersing at 25°C for 30 min to obtain the precursor. The precursor system was then adjusted to pH 2.8 with acetic acid, and a sol-gel reaction was carried out at 25°C for 40 min. The temperature was then raised to 70°C and stirred at 300 r / min for 2 h. Finally, the system was subjected to vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing: -0.09 MPa) for 20 min to obtain a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor. The mass ratio of the siloxane ceramic precursor, anhydrous ethanol, and water was 1:1.2:0.2.

[0053] The preparation of the titanate-modified nano-Al2O3 is as follows: 100g of nano-Al2O3 (particle size 50~80nm) is placed in a vacuum drying oven at 120℃ and dried for 2h to remove surface adsorbed water. 100g of the dried nano-Al2O3 is weighed and added to 500mL of anhydrous ethanol, and ultrasonically dispersed for 30min to obtain a uniform nano-Al2O3 suspension. The titanate coupling agent (isopropyltris(dioctylpyrophosphoryloxy)titanate) is dissolved in anhydrous ethanol, and the amount of titanate coupling agent is 4% of the mass of nano-Al2O3, to prepare a 10% titanate coupling agent ethanol solution. Under stirring conditions (500r / min), the titanate coupling agent ethanol solution is slowly added dropwise (dropping rate 1mL / min) to the nano-Al2O3 suspension. After the addition is complete, the temperature is raised to 80℃ and the reaction is carried out at a constant temperature with stirring for 2h. After the reaction was completed, the mixture was filtered under reduced pressure. The filter cake was washed three times with anhydrous ethanol to remove unreacted titanate coupling agent. Then, the filter cake was dried in a vacuum drying oven at 80°C for 12 hours, ground and sieved to obtain titanate-modified nano-Al2O3, which was then sealed for later use.

[0054] The preparation of the rapid ceramic coating in this embodiment includes the following steps: ① Mix 100g of anhydrous ethanol and 80g of ethyl acetate to obtain a mixed dispersion solvent. Add 30g of aminated carbon nanotubes, 45g of titanate-modified nano-Al2O3 and 15g of graphene nanosheets to the mixed dispersion solvent and ultrasonically disperse at an ultrasonic power of 800W for 40min to obtain a synergistically reinforced phase dispersion.

[0055] ② The grafted modified matrix, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, and borosilicate glass powder were stirred for 30 min at 60℃ and 300 r / min. Then, the synergistic reinforcing phase dispersion, 8 g of KH550, 12 g of diethylenetriamine, 7 g of BYK-333 leveling agent, and 8 g of fumed silica were added and stirred for 1 h at 60℃ and 300 r / min. Then, the mixture was ultrasonically dispersed for 30 min at an ultrasonic power of 800 W. Finally, the mixture was degassed under vacuum (vacuum degree of degassed -0.09 MPa) for 30 min to obtain the coating composition.

[0056] ③ The surface of the carbon fiber composite vehicle body substrate was sanded with 400-grit sandpaper, wiped with anhydrous ethanol to remove oil, vacuum dried at 60℃ for 30 minutes, and then cooled to room temperature; gradient coating was carried out using an air spraying process (spraying pressure 0.4MPa): the coating composition obtained in steps ① and ② above was diluted to slurries with solid contents of 35wt% and 45wt% respectively using a mixed dispersion solvent composed of anhydrous ethanol and ethyl acetate at a mass ratio of 5:4. The slurries with solid contents of 35wt% and 45wt% were sprayed sequentially on the surface of the carbon fiber composite vehicle body substrate to form an inner layer (base coat) with a thickness of 30μm and an outer layer (top coat) with a thickness of 70μm respectively. After each layer was sprayed, it was leveled at room temperature (leveling of the inner layer for 15 minutes and the outer layer for 20 minutes) to obtain a coated substrate with a total coating thickness of 100μm.

[0057] ④ Place the coated substrate in an oven and cure it according to the following procedure: first, keep it at 60℃ for 2.5h, then raise the temperature to 90℃ at a rate of 2℃ / min and keep it at 90℃ for 1.5h. After curing, let it cool naturally to room temperature. In this way, a rapid ceramic coating is prepared on the surface of the carbon fiber composite vehicle body substrate.

[0058] In this embodiment, the performance of the prepared rapid ceramic coating was tested, and the results are shown in Table 2 below.

[0059] Table 2 In this embodiment, the impact resistance of the rapid ceramicization coating was measured to be 50 cm·kg (referring to GB / T 1732-2020, using a 1 kg hammer with an impact height of 50 cm), and the coating showed no cracking or peeling. Artificial climate aging (1000 h) was conducted according to the GB / T 1865-2009 test standard. Neutral salt spray resistance was conducted according to the GB / T 1771-2007 test standard. In Table 2, the coating peeling rate was determined as follows: the sample coated with the rapid ceramicization coating was placed in a high and low temperature alternating test chamber, heated to 80℃ at a heating rate of 5℃ / min and held for 30 min, and then cooled to -40℃ at a cooling rate of 10℃ / min and held for 30 min. This cycle was repeated 100 times. After removing the sample, the percentage of the coating peel area to the total coating area was measured. In Table 2, the oxidation resistance time of the coating in a static air atmosphere at 700℃ refers to the quantitative determination of the oxidation weight gain per unit area of ​​the sample coated with the rapid ceramicization coating under static air atmosphere conditions. When the cumulative oxidation weight gain per unit area of ​​the coating-substrate sample reaches 10 mg / cm³, the oxidation resistance time is determined. 2When the coating peels off or penetrates through cracks on the sample surface during the test, it is considered to have failed to resist oxidation, regardless of the weight gain. According to this criterion, the oxidation resistance time of the rapid ceramic coating of Example 2 of the present invention is 120 min in a static air atmosphere at 700°C.

[0060] This embodiment achieves a balance between ceramization performance and coating toughness by increasing the proportion of DOPO grafted modified epoxy resin and introducing a flexible plasticizer. The measured impact resistance reaches 50 cm·kg, fully meeting the operating requirements of high-speed rail car bodies. The measured interfacial shear strength is 32 MPa, and no significant defects were observed after high and low temperature cycling and neutral salt spray tests. The simplified two-stage air spraying process is suitable for industrial mass production, and the coating combines rapid ceramization, excellent weather resistance, and corrosion resistance, fully meeting all protection standards for high-speed rail carbon fiber composite material car bodies.

[0061] Example 3 This embodiment provides a rapid ceramic coating suitable for the surface protection of the leading edge of aerospace glass fiber composite wings and its preparation method.

[0062] The raw materials for preparing the rapid ceramic coating in this embodiment include a coating composition. This coating composition is designed to meet the requirements of high-speed airflow erosion, high-temperature ablation, and chemical resistance at the leading edge of aerospace glass fiber composite wings. The formulation is as follows: The grafted modified matrix is ​​obtained by mixing 370g of KH560 and KH570 double-grafted modified methylphenyl silicone resin and 80g of DOPO grafted modified epoxy resin, and stirring for 1h at a speed of 400r / min and a temperature of 60℃; the rapid ceramicization core phase is composed of 260g of chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and 65g of boron aluminosilicate glass powder (the boron aluminosilicate glass powder has a boron mass percentage of 4%); the synergistic reinforcing phase is composed of 45g of aminated carbon nanotubes, 65g of titanate modified nano-Al2O3 and 25g of graphene nanosheets; the functional additives are composed of 12g of KH550, 16g of diethylenetriamine, 4g of leveling agent BYK-333 and 12g of fumed silica; the mixed dispersion solvent is composed of 70g of anhydrous ethanol and 60g of ethyl acetate.

[0063] The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin, with a mass ratio of KH560 to KH570 of 2.75:1. The sum of the mass amounts of KH560 and KH570 is 8.1% of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. The preparation method is as follows: the hydroxyl-terminated methylphenyl silicone resin is heated to 90°C to melt, and then an acetic acid aqueous solution with a pH of 4.5 is uniformly sprayed onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activated at 90°C for 30 minutes to obtain a modified resin with a surface rich in silanol groups. The mass ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is 15 mL: 100 g. An ethanol aqueous solution (the ethanol aqueous solution is composed of anhydrous ethanol and water in a certain proportion) is used. A silane coupling agent solution was prepared by mixing KH560 and KH570 in a volume ratio of 9:1 (the total mass percentage of KH560 and KH570 in the silane coupling agent solution was 3%). Then, acetic acid was added to adjust the pH of the silane coupling agent solution to 4.5 and pre-hydrolyzed for 40 min to obtain a pre-hydrolyzed silane coupling agent solution. The modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate (the amount of dibutyltin dilaurate catalyst was 0.027% of the mass of the hydroxyl-terminated methylphenyl organosilicon resin) were mixed evenly and reacted at a speed of 400 r / min and a temperature of 90℃ for 3 h. After cooling to 60℃, vacuum degassing (vacuum degree of vacuum degassing -0.09 MPa) was performed for 30 min to obtain KH560 and KH570 double-grafted modified methylphenyl organosilicon resin, which was sealed for later use.

[0064] The preparation of the DOPO graft-modified epoxy resin includes: preheating E51 epoxy resin at 70°C for 1 hour; dissolving 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone (the ratio of DOPO to N-methylpyrrolidone is 25:75) to obtain an N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO; and further dissolving the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone. The N-methylpyrrolidone solution of 10-phosphaphenanthrene-10-oxide (DOPO) containing 22.5% of the mass of E51 epoxy resin was slowly added dropwise (1 mL / min) to preheated E51 epoxy resin. Then, 0.125% of the mass of E51 epoxy resin triphenylphosphine catalyst was added. The mixture was heated to 140 °C and stirred for 4 h under nitrogen protection at a speed of 500 r / min. After vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing -0.09 MPa) for 20 min, DOPO-grafted modified epoxy resin was obtained and sealed for later use.

[0065] The preparation of the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor (methylphenyl silicone resin) in anhydrous ethanol, then adding water (deionized water), lanthanum nitrate hexahydrate, and ytterbium nitrate pentahydrate (the mass ratio of lanthanum nitrate hexahydrate to ytterbium nitrate pentahydrate is 5:2, and the total amount of lanthanum nitrate hexahydrate and ytterbium nitrate pentahydrate is 2.69% of the mass of the siloxane ceramic precursor), and ultrasonically dispersing at 25°C for 30 min to obtain the precursor. The precursor system was then adjusted to pH 2.8 with acetic acid, and a sol-gel reaction was carried out at 25°C for 40 min. The temperature was then raised to 70°C and stirred at 300 r / min for 2 h. Finally, the system was subjected to vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing: -0.09 MPa) for 20 min to obtain a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor. The mass ratio of the siloxane ceramic precursor, anhydrous ethanol, and water was 1:1.2:0.2.

[0066] The preparation of the titanate-modified nano-Al2O3 is as follows: 100g of nano-Al2O3 (particle size 50~80nm) is placed in a vacuum drying oven at 120℃ and dried for 2h to remove surface adsorbed water. 100g of the dried nano-Al2O3 is weighed and added to 500mL of anhydrous ethanol, and ultrasonically dispersed for 30min to obtain a uniform nano-Al2O3 suspension. The titanate coupling agent (isopropyltris(dioctylpyrophosphoryloxy)titanate) is dissolved in anhydrous ethanol, and the amount of titanate coupling agent is 4% of the mass of nano-Al2O3, to prepare a 10% titanate coupling agent ethanol solution. Under stirring conditions (500r / min), the titanate coupling agent ethanol solution is slowly added dropwise (dropping rate 1mL / min) to the nano-Al2O3 suspension. After the addition is complete, the temperature is raised to 80℃ and the reaction is stirred at a constant temperature for 2h. After the reaction was completed, the mixture was filtered under reduced pressure. The filter cake was washed three times with anhydrous ethanol to remove unreacted titanate coupling agent. Then, the filter cake was dried in a vacuum drying oven at 80°C for 12 hours, ground and sieved to obtain titanate-modified nano-Al2O3, which was then sealed for later use.

[0067] The preparation of the rapid ceramic coating in this embodiment includes the following steps: ① Mix 70g of anhydrous ethanol and 60g of ethyl acetate to obtain a mixed dispersion solvent. Add 45g of aminated carbon nanotubes, 65g of titanate-modified nano-Al2O3, and 25g of graphene nanosheets to the mixed dispersion solvent and ultrasonically disperse at an ultrasonic power of 800W for 40min to obtain a synergistically reinforced phase dispersion.

[0068] ② The grafted modified matrix, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, and borosilicate glass powder were stirred for 30 min at 65℃ and 300 r / min. Then, the synergistic reinforcing phase dispersion, 12 g of KH550, 16 g of diethylenetriamine, 4 g of BYK-333 leveling agent, and 12 g of fumed silica were added and stirred for 1.5 h at 65℃ and 300 r / min. The mixture was then ultrasonically dispersed for 30 min at an ultrasonic power of 800 W. Finally, the mixture was degassed under vacuum (vacuum degree of degassed -0.09 MPa) for 30 min to obtain the coating composition.

[0069] ③ The surface of the glass fiber composite wing leading edge substrate was sanded with 400-grit sandpaper, wiped with anhydrous ethanol-acetone solvent (anhydrous ethanol to acetone volume ratio 1:1) to remove oil, vacuum dried at 80℃ for 1 hour, and then cooled to room temperature; gradient coating was performed using a high-pressure spraying process (spraying pressure 15MPa): the coating composition obtained in steps ① and ② above was diluted to slurries with solid contents of 35wt%, 55wt%, and 60wt% respectively using a mixed dispersion solvent composed of anhydrous ethanol and ethyl acetate at a mass ratio of 3.5:3. The slurries with solid contents of 35wt%, 55wt%, and 60wt% were sprayed sequentially onto the surface of the glass fiber composite wing leading edge substrate to form an inner layer (base coat) with a thickness of 25μm, an intermediate layer with a thickness of 60μm, and an outer layer (top coat) with a thickness of 35μm. After each layer was sprayed, it was leveled at room temperature (leveling for 15 minutes for the inner layer, intermediate layer, and outer layer respectively), resulting in a coated substrate with a total coating thickness of 120μm.

[0070] ④ Place the coated substrate in an oven and cure it according to the following procedure: first, keep it at 60℃ for 2 hours, then raise the temperature to 100℃ at a rate of 2℃ / min and keep it at 1 hour, then raise the temperature to 120℃ at a rate of 2℃ / min and keep it at 1.5 hours. During the entire curing process, the curing pressure is 0.3MPa. After curing, allow it to cool naturally to room temperature. This process prepares a rapid ceramic coating on the surface of the glass fiber composite wing leading edge substrate.

[0071] In this embodiment, the performance of the rapidly ceramicized coating was tested, and the results are shown in Table 3 below.

[0072] Table 3

[0073] In Table 3, chemical resistance was tested according to GB / T 3857-2017 standard, and high-speed airflow erosion resistance was tested according to GJB 323A-96 standard. In Table 3, the oxidation resistance time of the coating in a static air atmosphere at 1100℃ refers to the quantitative determination of the oxidation weight gain per unit area of ​​the sample coated with the rapid ceramicization coating under static air atmosphere conditions. When the cumulative oxidation weight gain per unit area of ​​the coating-substrate sample reaches 10 mg / cm³, the oxidation resistance time is determined. 2 When the coating peels off or penetrates through cracks on the sample surface during the test, it is considered to have failed to resist oxidation. According to this criterion, the rapid ceramic coating of Example 3 of the present invention has an oxidation resistance time of 180 min in a static air atmosphere at 1100℃.

[0074] This embodiment achieves an ultrafast ceramization rate and ultra-high ablation resistance. Tested according to GJB 323A-96 standard, the linear ablation rate at 1300℃ is only 0.05 mm / s, demonstrating excellent resistance to Mach 3 high-speed airflow erosion. Simultaneously, the interfacial shear strength is measured to be as high as 40 MPa, and the microcrack width of the ceramized coating is <2 μm after 10 minutes of oxy-acetylene ablation at 1300℃. The coating exhibits excellent corrosion resistance to media such as aviation kerosene and hydraulic oil, fully meeting the extreme environmental protection requirements of aircraft wing leading edges. All performance characteristics comply with the application standards for aerospace composite material coatings.

[0075] Example 4 Example 4 is basically the same as Example 1, except that: The preparation of the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor (methylphenyl silicone resin) in anhydrous ethanol, then adding water (deionized water), lanthanum nitrate hexahydrate, and ytterbium nitrate pentahydrate (the mass ratio of lanthanum nitrate hexahydrate to ytterbium nitrate pentahydrate is 4:1, and the total amount of lanthanum nitrate hexahydrate and ytterbium nitrate pentahydrate is 4% of the mass of the siloxane ceramic precursor), and ultrasonically dispersing at 25°C for 30 min to obtain the precursor system. Then, acetic acid was added to adjust the pH of the precursor system to 2.8, and a sol-gel reaction was carried out at 25°C for 40 min. The temperature was then raised to 70°C and stirred at 300 r / min for 2 h. Finally, the system was subjected to vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing: -0.09 MPa) for 20 min to obtain a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor. The mass ratio of the siloxane ceramic precursor, anhydrous ethanol, and water was 1:1.2:0.2.

[0076] Example 5 Example 5 is basically the same as Example 1, except that: The preparation of the chemically bonded rare-earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor (methylphenyl silicone resin) in anhydrous ethanol, then adding water (deionized water), lanthanum nitrate hexahydrate, and ytterbium nitrate pentahydrate (the mass ratio of lanthanum nitrate hexahydrate to ytterbium nitrate pentahydrate is 4:1, and the total amount of lanthanum nitrate hexahydrate and ytterbium nitrate pentahydrate is 1% of the mass of the siloxane ceramic precursor), and ultrasonically dispersing at 25°C for 30 min to obtain the precursor system. Then, acetic acid was added to adjust the pH of the precursor system to 2.8, and a sol-gel reaction was carried out at 25°C for 40 min. The temperature was then raised to 70°C and stirred at 300 r / min for 2 h. Finally, the system was subjected to vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing: -0.09 MPa) for 20 min to obtain a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor. The mass ratio of the siloxane ceramic precursor, anhydrous ethanol, and water was 1:1.2:0.2.

[0077] Example 6 Example 6 is basically the same as Example 1, except that: The synergistic reinforcing phase consists of 60g of aminated carbon nanotubes, 40g of titanate-modified nano-Al2O3, and 20g of graphene nanosheets.

[0078] Example 7 Example 7 is basically the same as Example 1, except that: The grafted modified base material is obtained by mixing 405g of KH560 and KH570 double-grafted modified methylphenyl silicone resin and 45g of DOPO grafted modified epoxy resin, and stirring for 1h at a speed of 400r / min and a temperature of 60℃.

[0079] Example 8 Example 8 is basically the same as Example 1, except that: The grafted modified base material is obtained by mixing 225g of KH560 and KH570 double-grafted modified methylphenyl silicone resin and 225g of DOPO grafted modified epoxy resin, and stirring for 1h at a speed of 400r / min and a temperature of 60℃.

[0080] Example 9 Example 9 is basically the same as Example 1, except that: The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin. The mass ratio of KH560 to KH570 is 2:2.5, and the sum of the mass amounts of KH560 and KH570 is 8.57% of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. The preparation method is as follows: the hydroxyl-terminated methylphenyl silicone resin is heated to 90°C to melt, and then an acetic acid aqueous solution with a pH of 4.5 is uniformly sprayed onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activated at 90°C for 30 minutes to obtain a modified resin with a surface rich in silanol groups. The mass ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is 15 mL:100 g. An ethanol aqueous solution (the ethanol aqueous solution is composed of anhydrous ethanol and water in a specific ratio) is used. A silane coupling agent solution was prepared by mixing KH560 and KH570 in a product ratio of 9:1 (the total mass percentage of KH560 and KH570 in the silane coupling agent solution was 3%). Then, acetic acid was added to adjust the pH of the silane coupling agent solution to 4.5 and pre-hydrolyzed for 40 min to obtain a pre-hydrolyzed silane coupling agent solution. The modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate (the amount of dibutyltin dilaurate catalyst was 0.028% of the mass of the hydroxyl-terminated methylphenyl organosilicon resin) were mixed evenly and reacted at a speed of 400 r / min and a temperature of 90℃ for 3 h. After cooling to 60℃, vacuum degassing (vacuum degree of vacuum degassing -0.09 MPa) was performed for 30 min to obtain KH560 and KH570 double-grafted modified methylphenyl organosilicon resin, which was sealed for later use.

[0081] Example 10 Example 10 is basically the same as Example 1, except that: The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin. The mass ratio of KH560 to KH570 is 2:1, and the sum of the mass amounts of KH560 and KH570 is 3% of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. The preparation method is as follows: the hydroxyl-terminated methylphenyl silicone resin is heated to 90°C to melt, and then an acetic acid aqueous solution with a pH of 4.5 is uniformly sprayed onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activated at 90°C for 30 minutes to obtain a modified resin with a surface rich in silanol groups. The mass ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is 15 mL: 100 g. An ethanol aqueous solution (the ethanol aqueous solution is composed of anhydrous ethanol and water in a volume ratio of...) is used... A silane coupling agent solution was prepared by mixing KH560 and KH570 in a 9:1 ratio (the total mass percentage of KH560 and KH570 in the silane coupling agent solution was 3%). Then, acetic acid was added to adjust the pH of the silane coupling agent solution to 4.5 and pre-hydrolyzed for 40 min to obtain a pre-hydrolyzed silane coupling agent solution. The modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate (the amount of dibutyltin dilaurate catalyst was 0.028% of the mass of the hydroxyl-terminated methylphenyl organosilicon resin) were mixed evenly and reacted at 400 r / min and 90℃ for 3 h. After cooling to 60℃, vacuum degassing (vacuum degree of vacuum degassing was -0.09 MPa) was performed for 30 min to obtain KH560 and KH570 double-grafted modified methylphenyl organosilicon resin, which was sealed for later use.

[0082] Example 11 Example 11 is basically the same as Example 1, except that: The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin. The mass ratio of KH560 to KH570 is 2:1, and the sum of the mass amounts of KH560 and KH570 is 15% of the mass amount of the hydroxyl-terminated methylphenyl silicone resin. The preparation method is as follows: the hydroxyl-terminated methylphenyl silicone resin is heated to 90°C to melt, and then an acetic acid aqueous solution with a pH of 4.5 is uniformly sprayed onto the surface of the hydroxyl-terminated methylphenyl silicone resin and acid-activated at 90°C for 30 minutes to obtain a modified resin with a surface rich in silanol groups. The mass ratio of the acetic acid aqueous solution to the hydroxyl-terminated methylphenyl silicone resin is 15 mL: 100 g. An ethanol aqueous solution (the ethanol aqueous solution is composed of anhydrous ethanol and water in a volume ratio of...) is used... A silane coupling agent solution was prepared by mixing KH560 and KH570 in a 9:1 ratio (the total mass percentage of KH560 and KH570 in the silane coupling agent solution was 3%). Then, acetic acid was added to adjust the pH of the silane coupling agent solution to 4.5 and pre-hydrolyzed for 40 min to obtain a pre-hydrolyzed silane coupling agent solution. The modified resin, the pre-hydrolyzed silane coupling agent solution, and dibutyltin dilaurate (the amount of dibutyltin dilaurate catalyst was 0.028% of the mass of the hydroxyl-terminated methylphenyl organosilicon resin) were mixed evenly and reacted at 400 r / min and 90℃ for 3 h. After cooling to 60℃, vacuum degassing (vacuum degree of vacuum degassing was -0.09 MPa) was performed for 30 min to obtain KH560 and KH570 double-grafted modified methylphenyl organosilicon resin, which was sealed for later use.

[0083] Example 12 Example 12 is basically the same as Example 1, except that: The preparation of the DOPO graft-modified epoxy resin includes: preheating E51 epoxy resin at 70°C for 1 hour; dissolving 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone (the mass ratio of DOPO to N-methylpyrrolidone is 25:75) to obtain an N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO; and dissolving the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone. The N-methylpyrrolidone solution of DOPO (containing 5% of the mass of E51 epoxy resin) was slowly added dropwise (1 mL / min) to preheated E51 epoxy resin. Then, 0.1% of the mass of E51 epoxy resin of triphenylphosphine catalyst was added. The mixture was heated to 140 °C and stirred for 4 h under nitrogen protection at a speed of 500 r / min. After vacuum distillation and vacuum degassing (vacuum degree of vacuum degassing -0.09 MPa) for 20 min, DOPO grafted epoxy resin was obtained and sealed for later use.

[0084] Example 13 Example 13 is basically the same as Example 1, except that: The preparation of the DOPO graft-modified epoxy resin includes: preheating E51 epoxy resin at 70°C for 1 hour; dissolving 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone (the mass ratio of DOPO to N-methylpyrrolidone is 25:75) to obtain an N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO; and dissolving the 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide DOPO in N-methylpyrrolidone. The N-methylpyrrolidone solution of DOPO (containing 30% of the mass of E51 epoxy resin) was slowly added dropwise (at a rate of 1 mL / min) to preheated E51 epoxy resin. Then, 0.1% of the mass of E51 epoxy resin of triphenylphosphine catalyst was added. The mixture was heated to 140 °C and stirred for 4 h under nitrogen protection at a speed of 500 r / min. After vacuum distillation and vacuum degassing (vacuum degree of degassing: -0.09 MPa) for 20 min, DOPO-grafted modified epoxy resin was obtained and sealed for later use.

[0085] Comparative Example 1 Comparative Example 1 is basically the same as Example 1, except that: The rapid ceramicization core phase consists of 245g of siloxane ceramic precursor (methylphenyl silicone resin) and 60g of boron aluminosilicate glass powder (the boron aluminosilicate glass powder contains 4% boron by mass).

[0086] Comparative Example 2 Comparative Example 2 is basically the same as Example 1, except that: The rapid ceramization core phase is 305g of a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor.

[0087] Comparative Example 3 Comparative Example 3 is basically the same as Example 1, except that: The synergistic reinforcing phase consists of 40g of aminated carbon nanotubes, 60g of nano-Al2O3, and 20g of graphene nanosheets.

[0088] Comparative Example 4 Comparative Example 4 is basically the same as Example 1, except that: The grafted modified base material in Example 1 was replaced with a base material for the experiment. The base material was obtained by mixing 350g of methylphenyl silicone resin and 100g of epoxy resin E51 and stirring for 1h at a speed of 400r / min and a temperature of 60℃.

[0089] Comparative Example 5 Comparative Example 5 is basically the same as Example 1, except that: The coating composition does not contain a synergistic reinforcing phase.

[0090] The preparation of the rapid ceramization coating in this comparative example includes the following steps: ① Mix 120g of anhydrous ethanol with 80g of ethyl acetate to obtain a mixed dispersion solvent.

[0091] ② The grafted modified base material, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, and borosilicate glass powder were stirred for 30 min at 60℃ and 300 r / min. Then, the mixed dispersion solvent obtained in step ①, 10 g of KH550, 15 g of diethylenetriamine, 5 g of BYK-333 leveling agent, and 10 g of fumed silica were added and stirred for 1 h at 60℃ and 300 r / min. Then, the mixture was ultrasonically dispersed for 30 min at an ultrasonic power of 800 W. Finally, the mixture was degassed under vacuum (vacuum degree of degassed -0.09 MPa) for 30 min to obtain the coating composition.

[0092] ③ is the same as step ③ in Example 1.

[0093] ④ is the same as step ④ in Example 1.

[0094] Comparative Example 6 Comparative Example 6 is basically the same as Example 1, except that: ③ The surface of the rocket engine epoxy phenolic resin-based composite nozzle substrate was sanded with 400-grit sandpaper, wiped with anhydrous ethanol to remove oil, vacuum dried at 80℃ for 1 hour, and then cooled to room temperature; a high-pressure spraying process (spraying pressure 15MPa) was used for a single coating: the coating composition obtained in steps ① and ② was diluted to a slurry with a solid content of 50wt% using a mixed dispersion solvent composed of anhydrous ethanol and ethyl acetate at a mass ratio of 3:2. The slurry with a solid content of 50wt% was sprayed onto the surface of the rocket engine epoxy phenolic resin-based composite nozzle substrate to form a coating with a total thickness of 150μm. After leveling at room temperature for 40 minutes, the coated substrate was obtained.

[0095] The present invention conducted performance comparison tests on Examples 1, 4-13 and Comparative Examples 1-6, and the results are shown in Table 4.

[0096] Table 4

[0097] The data in Table 4 are tested using the same methods and conditions as those in Table 1; in Table 4, the symbol " / " indicates that the performance indicator was not tested.

[0098] The parts of this invention not described in detail are techniques known to those skilled in the art.

[0099] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A rapid ceramic coating, characterized in that, The raw materials for preparing the rapid ceramic coating include a coating composition, which comprises the following components in weight percentage: The composition includes 35-50% grafted modified matrix, 25-35% rapid ceramization core phase, 9-25% synergistic reinforcing phase, 3-8% functional additives, and 12-25% mixed dispersion solvent; The grafted modified base material is composed of KH560 and KH570 double-grafted modified methylphenyl silicone resin and DOPO grafted modified epoxy resin in a mass ratio of (1.5~5):

1. The raw materials for preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin include KH560, KH570 and hydroxyl-terminated methylphenyl silicone resin. The rapid ceramicization core phase is composed of a chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor and boroaluminosilicate in a mass ratio of 4:(0.5~1.5). The raw materials for preparing the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor include siloxane ceramic precursor, lanthanum nitrate and ytterbium nitrate. The synergistic reinforcing phase is composed of aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets.

2. The rapid ceramic coating according to claim 1, characterized in that: In preparing the KH560 and KH570 double-grafted modified methylphenyl silicone resin, the mass ratio of KH560 to KH570 is 2:(0.5~1.5), and the sum of the mass amounts of KH560 and KH570 is 5~10% of the mass amount of hydroxyl-terminated methylphenyl silicone resin.

3. The rapid ceramic coating according to claim 1, characterized in that: The raw materials for preparing the DOPO graft-modified epoxy resin include 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide and epoxy resin, wherein the mass amount of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide is 10~22.5% of the mass amount of epoxy resin.

4. The rapid ceramic coating according to claim 1, characterized in that: In preparing the chemically bonded rare-earth La and Yb co-doped siloxane ceramic precursor, the sum of the mass amounts of lanthanum nitrate and ytterbium nitrate is 1.5~2.8% of the mass amount of the siloxane ceramic precursor, and the mass ratio of lanthanum nitrate to ytterbium nitrate is 4:(0.5~1.6); and / or The boron aluminum silicate contains 3-5% boron by mass.

5. The rapid ceramization coating according to claim 1, characterized in that: In the synergistic reinforcing phase, the mass ratio of aminated carbon nanotubes, titanate-modified nano-Al2O3, and graphene nanosheets is (1.8~2.2):(2.5~3.5):

1.

6. The rapid ceramic coating according to claim 1, characterized in that: The functional additives include coupling agents, curing agents, leveling agents, and anti-settling agents, wherein the mass ratio of the coupling agent, curing agent, leveling agent, and anti-settling agent is (1~3):(1~2):(0.3~1):(0.5~2); and / or The mixed dispersion solvent consists of anhydrous ethanol and ethyl acetate.

7. A method for preparing a rapid ceramic coating according to any one of claims 1 to 6, characterized in that, The preparation method includes the following steps: (1) KH560 and KH570 double-grafted modified methylphenyl silicone resin was compounded with DOPO grafted modified epoxy resin to obtain grafted modified base material. (2) Aminated carbon nanotubes, titanate-modified nano-Al2O3 and graphene nanosheets were uniformly dispersed in a mixed dispersion solvent to obtain a synergistically reinforced phase dispersion. (3) The grafted modified base material, chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor, boroaluminosilicate, synergistic reinforcing phase dispersion and functional additives are mixed evenly to obtain a coating composition, and then the coating composition is formulated into a slurry. (4) A slurry is gradient coated on the surface of the composite matrix and cured, thereby preparing a rapid ceramic coating on the surface of the composite matrix.

8. The preparation method according to claim 7, characterized in that: The gradient coating involves applying 2-3 coats of a slurry with a solid content increasing sequentially within the range of 30-70 wt%; and / or The curing is a low-temperature segmented curing, which includes 2 to 3 stages of temperature increase curing, with the curing temperature increasing sequentially within the range of 60 to 120°C, and the total curing time is 2 to 5 hours.

9. The preparation method according to claim 7, characterized in that: The preparation of the KH560 and KH570 double-grafted modified methylphenyl silicone resin includes: heating hydroxyl-terminated methylphenyl silicone resin to 85-100℃ to melt it, then uniformly spraying an aqueous acetic acid solution with pH 4-5 onto the surface of the hydroxyl-terminated methylphenyl silicone resin and performing acid activation treatment at 85-100℃ for 20-40 min to obtain the modified resin; preparing a silane coupling agent solution by using an aqueous ethanol solution to KH560 and KH570, then adjusting the pH of the silane coupling agent solution to 4-5 and performing pre-hydrolysis for 20-60 min to obtain a pre-hydrolyzed silane coupling agent solution; mixing the modified resin, the pre-hydrolyzed silane coupling agent solution and dibutyltin dilaurate evenly and reacting at 85-100℃ and a rotation speed of 300-500 r / min for 3-3.5 h, followed by cooling and vacuum degassing to obtain the KH560 and KH570 double-grafted modified methylphenyl silicone resin.

10. The preparation method according to claim 7, characterized in that: The preparation of the DOPO grafted modified epoxy resin includes: preheating the epoxy resin, adding an N-methylpyrrolidone solution of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide to the preheated epoxy resin, then adding triphenylphosphine and reacting under inert gas protection at a temperature of 130~150℃ and a rotation speed of 400~600r / min for 3~6h, followed by vacuum distillation and vacuum degassing to obtain the DOPO grafted modified epoxy resin.

11. The preparation method according to claim 7, characterized in that: The preparation of the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor includes: dispersing the siloxane ceramic precursor in anhydrous ethanol, then adding water, lanthanum nitrate and ytterbium nitrate, and ultrasonically dispersing at 20-40℃ for 20-40 min to obtain the precursor system; then adjusting the pH of the precursor system to 2-3 to carry out a sol-gel reaction; then heating to 70-75℃ and stirring for 1-3 h; finally, obtaining the chemically bonded rare earth La and Yb co-doped siloxane ceramic precursor by vacuum distillation and degassing.

12. The application of the rapid ceramization coating according to any one of claims 1 to 6 or the rapid ceramization coating prepared by the preparation method according to any one of claims 7 to 11 in the surface protection of composite material parts, characterized in that, The composite material parts include carbon fiber composite parts, epoxy phenolic resin composite parts, or glass fiber composite parts.

Citation Information

Patent Citations

  • Preparation method of photocuring organic silicon modified epoxy resin paint film

    CN104761994A

  • High-temperature ceramic organosilicon-phenolic epoxy anticorrosive paint and preparation method thereof

    CN106893448A